The Relevance of Mitochondrial DNA Mutation in Human Diseases and Forensic Sciences: Review Article - Hussein Ali, Ruaa; Khaleel Hussein, Farhan; Majid Nasar, Dmoaa; Abd Al salam Salem, Asmaa (Al-Nahrain Journal of Science, 2025)
Several studies have been carried out on mitochondrial DNA mutation in human diseases. Mitochondria are self-contained organelles with their DNA. The primary function of mitochondria is oxidative phosphorylation (OXPHOS), which is how the Electron Transport Chain (ETC) provides energy to the cell. Reactive oxygen species (ROS), which can oxidative destroy DNA, proteins, and macromolecules like lipids, are one of the process’s potentially hazardous byproducts. Compared to mitochondrial DNA (mtDNA), nuclear DNA is better protective and has more repair mechanisms, making it more susceptible to oxidative damage that might result in mutations. This review focuses on the illnesses caused by mtDNA mutations known as "mitochondrial diseases. Numerous characteristics of (mtDNA), mainly those related to matrilineal heredity, a high duplicate number, and the absence of recombination, are advantageous for forensic study. Old bones, teeth, and hair are used as forensic samples for analysis, along with other biological samples with low levels of DNA. Different mtDNA haplogroups can affect longevity and risk of infection, in addition to being used to determine a person’s geographic origin.